Association between breakfast consumption frequency and handgrip strength and standing long jump: a systematic review and meta-analysis - Ren, Zhongyu; Zhang, Xiaoping; Wei, Yanqing; Liu, Shuai; Cao, Bing; Wang, Hejin (Frontiers in Psychology, 2024)
Over the past decade, numerous studies investigating the relationship between breakfast consumption frequency and handgrip strength and standing long jump have produced conflicting evidence, leading to uncertainty regarding this association. This study aimed to provide further clarity on the relationship between breakfast consumption frequency and handgrip strength and standing long jump. A comprehensive search of the literature up to September 15, 2023, was conducted on Web of Science, PubMed, Scopus, MEDLINE, and CNKI. Six studies related to grip strength and three studies related to standing long jump performance were included in the metaanalysis. For studies defining breakfast consumption frequency as an ordinal variable, the effect sizes of the lowest and highest frequency groups were analyzed. No significant differences in handgrip strength were found between the highest and lowest breakfast consumption groups. Furthermore, unlike in men, women with the highest frequency of breakfast consumption showed significantly higher handgrip strength levels than women with the lowest frequency of breakfast consumption. No significant positive associations were found between breakfast intake frequency and standing long jump levels. These results suggest that while regular breakfast consumption may enhance handgrip strength in women, it does not influence standing long jump performance in both sexes.